Check the picture below tell me if you understand what I did.
The answer: The 3 (three) consecutive odd integers are: -3, -1, 1.
_____________________________________________
Explanation:
_______________
To represent 3 (three consecutive odd integers):
____________________________________
Let "x" be the first odd integer.
____________________________________
Let "(x+2)" be next consecutive odd integer.
____________________________________
Let "(x+4") be the third odd integer.
____________________________________
The sum of these three consecutive odd integers:
__________________________________________
x + (x + 2) + (x + 4) = x + x + 2 + x + 4 = 3x + 6 ;
_________________________________________
Six ("6") times the sum of these 3 (three) consecutive odd integers =
_________________
6*(3x+6) = 6(3x + 6) = -18 (as given in the problem).
_____________________________________________
Given: 6(3x + 6) = -18 ; We can divide EACH SIDE of the equation by "6", to cancel the "6" on the left-hand side into a "1";
__________________________________________
{6(3x + 6) } / 6 = -18 / 6 ; to get:
________________________________________
3x + 6 = -3 ; Now, we can subtract "6" from EACH SIDE of the equation:
__________________________________
3x + 6 - 6 = -3 - 6 ; to get:
__________________________________
3x = -9 ; Now, we can divide EACH SIDE of the equation by "3"; to isolate "x" on one side of the question; and solve for "x" ;
___________________________________
3x / 3 = -9 / 3 ; x = - 3 ;
_____________________
Remember, from above:
__________________________
Let "x" be the first odd integer. We know that "x = -3".
Is this an odd integer? Yes!
____________________________________
Let "(x+2)" be next consecutive odd integer. So (x+2) = (-3+2) = -1.
Is this an odd integer? Yes! Is this "{-1}" the next consecutive odd integer with respect to "{-3}"? Yes!
____________________________________
Let "(x+4") be the third odd integer. So (x+4) = (-3+4) = 1.
Is this an odd integer? Yes! Is this "{1"} the next consecutive odd integer with respect to "{-1}"? Yes!
___________________________
So, our 3 (three) consecutive odd integers are: -3, -1, 1.
___________________________
To check our work: Is 6 times the sum of our 3 consecutive odd integers, equal to "(-18)" ?
The sum of our 3 consecutive odd integers = -3 + (-1) + 1 = -3 - 1 + 1 = -3.
6 * -3 = ? -18? Yes!
___________________________
Answer:
Here’s how you find the mean. Find the sum of all the data combined. Then divide the sum by how many numbers of data there are!!
Step-by-step explanation:
Answer:
z = -12
Step-by-step explanation:
The given system of equations is:
xy/(x + y) = 1 ...........................(1)
xz/(x + z) = 2...........................(2)
yz/(y + z) = 3...........................(3)
From (1): x + y = xy
=> y = xy - x
y = x(y - 1)
x = y/(y - 1).......................................(4)
From (2): 2(x + z) = xz
=> 2x + 2z = xz
2x = xz - 2z
2x = z(x - 2)
z = 2x/(x - 2) ....................................(5)
From (3): 3(y + z) = yz
=> 3y + 3z = yz
3y = yz - 3z
3y = z(y - 3)
z = 3y/(y - 3)....................................(6)
Comparing (5) and (6)
2x/(x - 2) = 3y/(y - 3)
2x(y - 3) = 3y(x - 2)
2xy - 6x = 3xy - 6y
6(y - x) = xy .................................(7)
But from (1): xy = x + y
Using this in (7), we have
6(y - x) = x + y
6y - y - 6x - x = 0
5y - 7x = 0
5y = 7x
x = 5y/7................................................(8)
Using this in (4)
5y/7 = y/(y - 1)
1/(y - 1) = 5/7
(y - 1) = 7/5
y = 1 + 7/5
y = 12/5..........................................(9)
Using this in (8)
x = 5(12/5)/7 = 12/7 .......................(10)
Using (10) in (5)
z = 2x/(x - 2)
z = 2(12/7) ÷ (12/7 - 2)
= 24/7 ÷ -2/7
= 24/7 × (-7/2)
= -24/2 = -12
z = -12.
Answer:
x=8 & x=6
Step-by-step explanation: